Audio in place: media, mobility & HCI: creating meaning in space - Chamberlain, Alan; Bødker, Mads; Hazzard, Adrian; Benford, Steve (ACM, 2016)
Audio-based content, location and mobile technologies can offer a multitude of interactional possibilities when combined in innovative and creative ways. It is important not to underestimate impact of the interplay between location, place and sound. Even if intangible and ephemeral, sounds impact upon the way in which we experience the built as well as the natural world. As technology offer us the opportunity to augment and access the world, mobile technologies offer us the opportunity to interact while moving though the world. They are technologies that can mediate, provide and locate experience in the world. Vision, and to some extent the tactile senses have been dominant modalities discussed in experiential terms within HCI. This workshop suggests that there is a need to better understand how sound can be used for shaping and augmenting the experiential qualities of places through mobile computing.